Enhanced cell migration and invasion of CD133+ pancreatic cancer cells cocultured with pancreatic stromal cells - Taiki Moriyama; Kenoki Ohuchida; Kazuhiro Mizumoto; Lin Cui; Naoki Ikenaga; Norihiro Sato; Masao Tanaka (2010)
Abstract BACKGROUND: Recently, cancer stem cells have been reported as a new therapeutic target in pancreatic cancer as well as other cancers, but the specific role of these cells is unknown. METHODS: The authors investigated the functional roles of CD133 + cells, 1 of the putative cancer stem cell candidates in pancreatic cancer. CD133 expression was assessed in human pancreatic cancer and cancer cell lines by quantitative real‐time reverse transcriptase polymerase chain reaction and flow cytometry. Next, they compared the ability of CD133 + and CD133 − cells to proliferate, migrate, and invade using 2 pancreatic cancer cell lines. In particular, they evaluated the relationship between CD133 + cells and primary pancreatic stromal cells. RESULTS: CD133 was expressed in primary human pancreatic cancer tissues and some cancer cell lines, whereas there was little expression in primary normal pancreatic epithelial cells and primary pancreatic stromal cells. CD133 + cells, isolated by flow cytometry, showed increased cell proliferation under anchorage‐independent conditions ( P < .01), and enhanced migration and invasion, particularly when cocultured with primary pancreatic stromal cells ( P < .001). Chemokine‐related receptor‐4 (CXCR4), markedly overexpressed in CD133 + cells, may be responsible for the increased invasive ability of the cells cocultured with pancreatic stromal cells, which express stromal derived factor‐1, the ligand to CXCR4. CONCLUSIONS: These data suggest that CD133 + cells exhibit more aggressive behavior, such as increased cell proliferation, migration, and invasion, especially in the presence of pancreatic stromal cells. The targeting therapy for the interaction between CD133 + cancer cells and stromal cells may be a new approach for the treatment of pancreatic cancer. Cancer 2010. © 2010 American Cancer Society.